Hubungan Tempat Penampungan Air dengan Keberadaan Jentik Aedes aegypti di Perumahan Dinas Type E Desa Motu Kecamatan Baras Kabupaten Mamuju Utara - Gafur, Abdul; Saleh, Muhammad (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
The presence of Aedes aegypti mosquito larvae in an area is an indicator of the presence of Aedes aegypti mosquito population in the area. The Aedes aegypti mosquitoes live and breed in the clean water storage containers that does not directly in contact with the ground such as bathtubs, bird waterers, water storage tanks, clay pots or barrels, cans, tires, and others. In District Baras Village Motu, The Dengue Hemorrhagic Fever cases annually have increased due to low participation of the community in reducing the number of larval populations, then this is what lies behind researchers to see the relationship of water storage containers with the presence of Aedes aegypti larvae. This study aims to determine the relationship of water storage containers with the presence of Aedes aegypti larvae in the official housing type E Village Motu Subdistrict Baras District Mamuju Utara in 2013. This type of research is an observational study with cross sectional design approach. Sampling was conducted using a survey technique with a sample of 642 water storage containers. The data were collected by taking primary and secondary data where the primary data were analyzed us-ing chi-square test. The results showed that there is a relationship between the type, location, material, color and cover of water storage containers in the presence of Aedes aegypti larvae with all values (P = 0.000) or P < α (0.005). Expected that the community to pay more attention to the implementation of activities 2M plus PSN-DBD independently and regularly according to standards in order to reduce the presence of mosquito larvae. With the implementation, then transmission of dengue fever can be suppressed. Keywords: water storage containers, the presence of larvae, larvae of Aedes aegypti.